Peningkatan Pengetahuan Siswa SMA terkait Permasalahan Kesehatan melalui Edukasi Waspada Penyakit Maag - Fadilla, Dea; Santoso, Khansa Kanastri; Fauziah, Fiha; Yanti Harahap, Novita Rahma; Hasibuan, Rapotan (Universitas Pahlawan Tuanku Tambusai, 2025)
Adolescents are a vulnerable age group prone to health problems due to irregular lifestyles, such as skipping breakfast, consuming unhealthy foods, and experiencing stress. One of the common disorders they face is gastritis. A survey conducted at SMA Negeri 1 Kecamatan Binjai, Langkat Regency, showed that 27% of students experienced gastritis symptoms within the past two months. This community service activity aimed to improve students’ knowledge about gastritis through health education. The method used was quasi-experimental with a one-group pre-test and post-test design involving 27 students from class X-7. The educational intervention was delivered interactively using PowerPoint presentations, posters, quizzes, and QA sessions. The results showed an increase in knowledge scores from 249 (92.22%) to 259 (95.93%), or an improvement of 3.71%. The most significant increase was in understanding the effects of smoking, excessive eating patterns, and stress. Health education proved effective and is essential to be conducted regularly to strengthen understanding and encourage healthy behavior among students.